THE MARKETING STRATEGY FOR ONLINE PREMARITAL MARRIAGE IN BIRO DINAMIS PSIKOLOGI - Aqilah Mufidah Suhadi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
The Marketing Strategy for Online Premarital Marriage in Biro Dinamis Psikologi Marriage essentially has become a sacral tradition on so many people’s life. This is the moment where people are officially commit to spend their life together forever. However, as the time pass by, the trend is now changing. Mostly, staarted from millenials and z generations, only several groups of people who are interested in marriage. There are so many factors of why the numbers of marriage in Indonesia is shrinking. The shifting idea of its marriage, the finantial condition, the unmatchable background of its couple, and the booming cheating issue have change they way people perceive its marriage. At this time, people become more cautious. It is neither bad nor good. It is a sign that people are finally aware that marriage is something that people can’t taking granted on. People can be seen so happy in the first year and have a child,yet they decideto divorce due to several reason. Therefore, it is important for people to have a plan and a consideration before getting into marriage. One of the plans is to have a mental premarital consultation, especially online session. Biro Dinamis Psikologi as the object here is providing the online premarital consultation as a new service. In summary, this research is studying about the suitable marketing strategy for Biro Dinamis Psikologi to gain more customers by conducting the aspect of consumer doubt, skepticism, familiarity, information seeking, value for money, and aesthetic design on its purchase intention. By doing this research, Biro Dinamis Psikologi and also the researcher can help it to find a new solution for its new online service together.